Material removal mechanism of multi-layer metal-film nanomilling. Issue 1 (2022) - Yan, Yongda; Wang, Jiqiang; Geng, Yanquan; Zhang, Guoxiong
Abstract: Tip-based nanomilling via atomic force microscopy enables alterable feature sizes for fabrication of substrates for surface-enhanced Raman scattering (SERS) with tunable plasmonic resonances. Specifically, nanomilling of SERS substrates on a multi-layer Au/Ag/Au film was investigated. The material removal mechanism at close-to-atomic scale, plastic deformation of the sample material, as well as the formation of nanogrooves were characterized. The Raman enhancement mechanism of the SERS substrate was revealed via simulations. This work thus provides a new method for preparing SERS substrates with tunable plasmonic resonances.